2021
DOI: 10.1016/j.ebiom.2021.103751
|View full text |Cite
|
Sign up to set email alerts
|

MUC2 and related bacterial factors: Therapeutic targets for ulcerative colitis

Abstract: The mucin2 (MUC2) mucus barrier acts as the first barrier that prevents direct contact between intestinal bacteria and colonic epithelial cells. Bacterial factors related to the MUC2 mucus barrier play important roles in the response to changes in dietary patterns, MUC2 mucus barrier dysfunction, contact stimulation with colonic epithelial cells, and mucosal and submucosal inflammation during the occurrence and development of ulcerative colitis (UC). In this review, these underlying mechanisms are summarized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 93 publications
2
69
0
Order By: Relevance
“…Occludin is one of the major intestinal tight junction proteins involved in maintaining the structural integrity of the colon ( 29 , 30 ), and is observed to be downregulated during colitis ( 31 ). In addition, deficiency in Muc2 expression leads to spontaneous development of colitis in mice, and diminished mucus production has been observed in IBD patients ( 32 , 33 ). Furthermore, mucin expression has been shown to be inversely correlated with IBD severity and inflammation levels in the gut ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Occludin is one of the major intestinal tight junction proteins involved in maintaining the structural integrity of the colon ( 29 , 30 ), and is observed to be downregulated during colitis ( 31 ). In addition, deficiency in Muc2 expression leads to spontaneous development of colitis in mice, and diminished mucus production has been observed in IBD patients ( 32 , 33 ). Furthermore, mucin expression has been shown to be inversely correlated with IBD severity and inflammation levels in the gut ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that intestinal epithelial barrier dysfunction and impaired tight junction function play a crucial role in pathogenesis of IBD (Sanchez de Medina et al, 2014;Mehandru and Colombel, 2021). Cell proliferation and the expression of tight junction-associated and peripheral membrane proteins (KI67, Occluding, Claudin-1, ZO-1, and MUC2) have been analyzed to determine intestinal barrier function (Tan and Zheng, 2018;Graefe et al, 2019;Yao et al, 2021). The slgA is the intestinal mucosal immune barrier's front line against external pathogens (Kumar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The mucus layer is formed by mucins combined with water, inorganic salts, and antimicrobial peptides, which could protect the gastrointestinal tract from invading pathogens and promote the development of the intestine ( 33 ). MUC2 is the main protein component of the intestinal mucus and can provide a physical barrier between the epithelium and the luminal content ( 34 ). The results of this study showed that the number of goblet cells in the intestine of the PNZ- and ZO-supplemented groups was increased.…”
Section: Discussionmentioning
confidence: 99%